Inovasi pembelajaran berbasis teori kecerdasan majemuk untuk pengembangan peran sekolah di era 4.0 - Priyambodo, Panggih (Universitas Negeri Yogyakarta, 2019)
Industrial Revolution Era 4.0 has brought disruption phenomena in various fields of life. The characteristics of the younger generation also experienced a shift, especially those that occurred in the millennial generation (gen Y) and generation Z. This condition encouraged schools as formal educational institutions to organize learning processes that can answer global challenges. Innovations in the learning process must be done continuously, one of them through the development of multiple intelligences and the involvement of learning technology elements. The development of multiple intelligences in the learning process requires the creativity of the teacher in selecting and determining the right models and learning strategies. The assessment instrument is not only directed at measuring cognitive aspects but also covers all aspects of competency as required by students. Learning patterns based on the development of multiple intelligences will be more effective if done by raising issues and real problems. Through an inquiry project, students will be actively involved in various forms of learning activities to make it an opportunity to bring up multiple types of abilities. The learning process, based on the development of multiple intelligences, is expected to be able to develop student competencies as a whole. The final result is the formation of adaptive individuals who are able to compete in the industrial revolution 4.0 era without having to leave their local culture.Era Revolusi Industri 4.0 telah membawa dampak fenomena disrupsi di berbagai bidang kehidupan. Karakteristik generasi muda juga mengalami pergeseran, terutama yang terjadi pada generasi milenial (gen Y) dan generasi Z. Kondisi ini mendorong sekolah sebagai lembaga pendidikan formal untuk menyelenggarakan proses pembelajaran yang mampu menjawab tantangan global. Inovasi dalam proses pembelajaran harus terus dilakukan salah satunya melalui pengembangan kecerdasan majemuk (multiple intelligences) serta pelibatan unsur teknologi pembelajaran. Pengembangan kecerdasan majemuk di dalam proses pembelajaran membutuhkan kreativitas dari para guru dalam memilih dan menetapkan model maupun strategi pembelajaran yang tepat. Instrumen penilaian juga tidak hanya diarahkan pada pengukuran aspek kognitif saja melainkan mencakup keseluruhan aspek kompetensi sebagaimana yang dibutuhkan peserta didik. Pola pembelajaran berbasis pengembangan kecerdasan majemuk akan lebih efektif jika dilakukan dengan mengangkat isyu-isyu maupun permasalahan nyata. Melalui proyek penyelidikan, peserta didik akan terlibat aktif di berbagai bentuk kegiatan belajar sehingga menjadikannya berkesempatan untuk memunculkan berbagai bentuk kemampuan. Proses pembelajaran berbasis pengembangan kecerdasan majemuk diharapkan mampu menumbuhkembangkan kompetensi peserta didik secara menyeluruh. Hasil akhirnya adalah terbentuknya individu-individu adaptif yang mampu bersaing di era revolusi industri 4.0 tanpa harus meninggalkan kultur lokalnya.